The judge's obligations in front of challenges of the constitutional precedents with regard to motivation of the judicial providences - Celis Galvis, María Laura (2016)
Judicial autonomy has suffered changes all through Colombian constitutional history, especially due to the expedition of the Political Constitution in 1991. This implies that the judge’s function was affected and suffered relevant changes, particularly in duties such as the motivation of judicial providences and the search for real justice in concrete cases. As a consequence of these relevant changes, now judges must pay special attention to the constitutional precedent and the charges imposed on them in order to avoid sanctions like the annulment of their judgments through the «vías de hecho» doctrine. These limitations and consequences were issued with the aim of protecting fundamental rights, and making the legal system dynamic and coherent.